Quality Assurance on Force Measurement of 1 MN Lever-Type Force Standard Machine Through System Check - hafid hafid; Dinar Nurcahyono (Instrumentasi, 2019)
Abstract— The 1 MN lever-type force standard machine operated by Research Center for Metrology Indonesian Institute of Sciences (RCM-LIPI) is the national standard for calibration of force measuring instruments from 2 kN to 1 MN measurement range. One of the assurances to ensure that the machine works well is through a system check. System check is carry out by comparing the force value generated by the machine to the force generated by the deadweight at capacity of 10 kN and 20 kN. In this paper, data is collected from the system check results from 2007 to 2016. Data processing is carried out by comparing the result and examining the variants similarities. Results showed that the |En| number results for all data spread from 0.00 to 0.91 with average 0.35 and variance of the system check results has variants similarities based on Fisher-test. These results indicate that the 1 MN lever-type force standard machine still has a good performance.